(3HZjI GdWdGHs - (3CHh YHO Gddg eMeO Hf CMeO Hf CHj jMji GdJdeSGfj GdMHGc,J (B867 (3g` s
(3ChdgG (B:s
(3HMeOc Gddge fXei CHJOi eUdjkG Ydi GdQShd CMeO hCQJLi Cf JLRdf KhGHi Ydi fXGe HZjI GdWdGH s
(3BNQgG (B:s
(3hcd eTJZd jhGRi GdXd ai fUa GdfgGQ eGjYhbI CYQa ef chcH Ch ZjQg bSeg HeJhSW cPG aGYQag s
(3Vef eLehY s
(3CQLhRI ai GdCSWQdGHs
(3cJHJ Hbde ajg VHWs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B114s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B332 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B365 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs